Video processing analysis for the determination and evaluation of the chemotactic response in bacterial populations - Nisenbaum, Melina (2016)
The aim of the present work was to design a methodology based on video processing to obtain indicators of bacterial population motility that allow the quantitative and qualitative analysis and comparison of the chemotactic phenomenon with different attractants in the agarosein plug bridge method. Video image sequences were processed applying Shannon's entropy to the intensity time series of each pixel, which conducted to a final pseudo colored image resembling a map of the dynamic bacterial clusters. Processed images could discriminate perfectly between positive and negative attractant responses at different periods of time from the beginning of the assay. An index of spatial and temporal motility was proposed to quantify the bacterial response. With this index, this video processing method allowed obtaining quantitative information of the dynamic changes in space and time from a traditional qualitative assay. We conclude that this computational technique, applied to the traditional agarosein plug assay, has demonstrated good sensitivity for identifying chemotactic regions with a broad range of motility.